Understanding supply chain management (scm) in industrialised building systems (ibs) in Malaysian construction - Mohammad, Mohammed Fadhil; Abd Shukor, Ani Saifuza; Mahbub, Rohana (2011)
IBS involves relationships among various organisations, and includes the evolution of many specialised roles and embedded players. However, the fragmentation and adversarial relationship scenario in the IBS of the Malaysian construction industry leaves supply chain players with noticeable difficulties in terms of integration competitiveness. Although efforts have been undertaken to enhance the IBS practice, establishing integration among IBS players remains a major hindrance due to the lack of supply chain procurement practices. Thus, the Malaysian IBS has been challenged to achieve supply chain integration to enhance the performance delivery of IBS projects. At the same time, the SCM concept has been recognised as a tool for achieving better integration amongst construction players. However, understanding SCM has become a hindrance in Malaysia. Various interpretations of the SCM concept make the process of achieving and supporting the entire SCM approach quite challenging. Considerable confusion also arises because SCM is viewed from a number of perspectives for several reasons. To improve the management and integration of the supply chain, understanding SCM is very important, and various problems and barriers of managing IBS supply chains must be addressed properly. Furthermore, to realise the government's aspiration, good approach and arrangement of supply chain should be investigated and fully established. The objectives of the present research project are to identify the understanding of SCM concepts, investigate current problems and barriers of SCM in IBS construction, and determine the approaches of IBS project within the supply chain in project delivery. To clarify the importance of implementation of the SCM concept, a literature review is presented. The review offers an analysis of the various definitions of SCM adopted by different sectors. The questionnaire survey is adopted to underpin the variables for understanding SCM and its key features as well as the purpose from the standpoint of IBS players. To establish understanding of the area to be studied, analysis of the approach of IBS project with regard to the arrangement of procurement methods being undertaken is performed through qualitative semi structured interviews. The findings highlight the need for evaluation of the development of SCM definitions and concepts because such development will partly influence the establishment of a suitable definition and understanding of SCM within the IBS construction industry. Furthermore, the findings show that the problems related to supply chain in the procurement implementation are common among players, especially in the construction and design stages, which have contributed to project delays and cost overrun. Findings also reveal that while both procurement approaches vary in their roles and responsibility to the individual project, management of supply chains remains as one of the key elements in all procurement methods. Finally, the findings will benefit both the academia and the Malaysian ISS project delivery players. These will provide new insights on the theoretical perspectives of supply chain integration in improving IBS construction.